2012
DOI: 10.4172/1948-5956.1000166
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Intra-patient Controlled Trial of Mepilex Lite Dressings versus Aqueous Cream in Managing Radiation-Induced Skin Reactions Postmastectomy

Abstract: Objective: Severe acute radiation-induced skin reactions occur in a significant proportion of women who receive radiation therapy for breast cancer. We previously showed that Mepilex Lite dressings decreased the severity of erythema. Here we report their effect on the full range of skin reactions in 74 breast cancer patients post-mastectomy. Methods:A total of 80 women were recruited from four hospitals in New Zealand with 74 women contributing a full data set for analysis. The first skin area on the chest wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 25 publications
3
45
0
7
Order By: Relevance
“…Therefore, nursing management in follow-up nursing clinics is directed toward the palliation of skin reaction symptoms (Porock, 1999). Other reports have identified five management trials that examined a range of products (corticosteroid creams, sucralfate cream, hydrocolloid dressings, and a moisture vapor permeable dressing) (Paterson, 2012). Based on these results, no agent was found that significantly reduced the impact of acute radiation-induced skin reactions.…”
Section: Results: a Personalized Skin Care Regimen Was Developed Withmentioning
confidence: 99%
“…Therefore, nursing management in follow-up nursing clinics is directed toward the palliation of skin reaction symptoms (Porock, 1999). Other reports have identified five management trials that examined a range of products (corticosteroid creams, sucralfate cream, hydrocolloid dressings, and a moisture vapor permeable dressing) (Paterson, 2012). Based on these results, no agent was found that significantly reduced the impact of acute radiation-induced skin reactions.…”
Section: Results: a Personalized Skin Care Regimen Was Developed Withmentioning
confidence: 99%
“…It provides additional data in addition to provider-observed assessments that reflect the patient's lived experience. The Radiation-Induced Skin Reaction Assessment Scale (RIS-RAS) (22) also incorporates a professional assessment scale and a patient-rated symptom scale and has been used successfully to measure the observer-based and patient-based skin reaction in several recent trials (23)(24)(25)(26). Because the Skindex-16 does not include a professional assessment, the STAT was also used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2 Namun saat ini belum terdapat obat yang bisa menjadi standar dalam penanganan reaksi kulit. 7,8 Cara mempertahankan hidrasi kulit dengan mengunakan berbagai moisturizer, krim barrier, aloe vera, lanolin, dan krim steroids. 9, 10 Peter menemukan bahwa sekitar 77,5% pasien sembuh dengan pemberian salep dan kompres basah.…”
Section: Pendahuluanunclassified